Devoções religiosas: negociações e disciplinamentos com e/do sagrado - Aguiar, Sylvana Maria Brandão de; Lima, Hélio Pereira (Anais dos Simpósios da ABHR, 2016)
Devoções religiosas: negociações e disciplinamentos com e/do sagrado